The Impact of Tabuh & pathet Gamelan Practice on Cognitive Aging in Older Adults - Kezia Karnila Putri; Vanessa Majesty; Alysia Widjaja (International Journal Labs, 2026)
Tabuh & pathet are among the most fundamental techniques that a gamelan player must master in order to play the instrument fluently. Tabuh refers to striking a gamelan key with a mallet using the dominant hand, while pathet refers to dampening the resonance of the key with the non-dominant hand to prevent it from sustaining too long. Executing proper tabuh & pathet within a melodic pattern (gendhing) demands sustained concentration, rapid cognitive processing, and the ability to recall which key to dampen at the appropriate moment. This cognitively demanding practice holds potential applications in music therapy, particularly for older adults who may benefit from structured activities that stimulate attentional control, bilateral motor coordination, and working memory. The purpose of this study was to evaluate the impact of practicing tabuh & pathet on the cognitive performance of older adults. Seven older adults without cognitive impairment participated in weekly introductory gamelan practice sessions conducted over a two-month period, accompanied by peer partners and a music therapist. Participants practiced the tabuh & pathet technique while learning melodic patterns (gendhing) aurally, without the use of visual aids or written notation. Cognitive performance was assessed using the Mini-Mental State Examination (MMSE) administered before and after the intervention. Following the two-month intervention, all participants demonstrated improvement in their MMSE post-test scores, suggesting that structured gamelan practice may serve as an effective form of cognitive stimulation for older adults.